Math 131BH: Honors Analysis Problem Set 1 due Wednesday, January 15 1. Prove part (c) of Theorem 6.12 on p.128 in Rudin. 2.

Let f, α : [a, b] → R be two monotone increasing functions. Suppose that f ∈ R (α). Show that α ∈ R (f ) and that
b b

f dα +
a a

αdf = f (b)α(b) − f (a)α(a).

3. Rudin, Exercise 3 on p.138. 4. Rudin, Exercise 8 on p.138. 5. Rudin, parts (a), (b), (c) of Exercise 10 on p.139. 6. Rudin, Exercise 11 on p.140. 7. Rudin, Exercise 13 on p.140.

f. f. f. α)) P P P as > 0 was arbitrary. α)) = P R b f dα c (which I will not prove here) from which the result follows. that is. let Q. f. [c. Hence. Let > 0 and let P be a partition of [a. f. f. f. α) − L(P . f. f. f. and we have U (P . f. we note that ˆ a b f dα = inf(U (P. (Theorem 6. 2) such that U (Q1 . α) − L(Q. α) − L(R. f. α) − inf (U (Q. R is a partition of [c. f ∈ R (α) on [a. α)) + inf (U (R. α). f. f. α) − L(P. α)) + 2 P P P so inf U (P . α) = inf (U (Q. Let P = P ∪{c}. c]. α)) where P ranges over all partitions of [a. b] and a < c < b. we have inf U (P . α) < inf (U (Q. f. f. b]. α) − L(P. α)) < P Then. α) < as both of these quantities are nonnegative. f. f. R2 be partitions of [a. α)) ≥ inf (U (Q. α)) + inf (U (R. α)) from which it follows that U (Q. To compute the integral. α)) = inf (U (R. f. f. Lastly. α) < as P is a renement of P . α). α) = U (Q. f. This can be replaced by inf(U (P . f. f. inf U (P . α) + U (R. α)) + inf (U (R. f. f. f. α) − L(Q. α) − inf (U (R. U (P . R be as above (so P = Q ∪ R) and note U (P . the partition formed from all the points of P and the point c. Show f ∈ R (α) on [a. Write P = Q ∪ R where Q = {x ∈ P : x ≤ c} and R = {x ∈ P : x ≥ c}. f. f. f. α)) = P Q ˆ a c f dα ˆ and inf (U (R. α)) ≤ inf (U (Q. α) − L(R. f. α)) + (U (R. f. inf (U (Q. α) + U (R. α) + U (R2 . Now. f. α) < . b] and ˆ a b ˆ f dα = a c ˆ f dα + c b f dα Solution. f. Q is a partition of [a. α) < and U (R. b] containing c as to every P we can associate P = P ∪{c} with U (P . c] and [c. α)) P P P let > 0 and let Q1 . 1 . α) = (U (Q. α)) < P and U (R2 . f. f. if P = Q1 ∪ R2 . f. To prove that inf (U (Q. α)) = inf (U (Q. α)) P P P P where we have identied P = Q ∪ R as above. b] arising from P1 and P2 (ie Pj = Qj ∪ Rj for j = 1. α)) + inf (U (R. f. f. c].12(c)) Let f ∈ R (α) on [a. f. α)−L(P . Hence. c] and [c. α) ≤ U (P. f. α) ≤ U (P. α) ≤ U (P . f. f. α) ≤ inf (U (Q. f. α) = U (Q1 . f. f. α)) where P ranges over all partitions of [a.Homework 1 Solutions that 1. Then. f. f. b]. α) + U (R. f. f. b] such that U (P. b]. Then. if P is such a partition.

α.xp+1 ] inf f (x)) as β1 (xj ) − β1 (xj −1 ) is 0 if j = p + 1 and 1 if j = p + 1. we see this expression is as claimed. for this P we also have U (P. β1 ) < . Then. b] → R be two increasing functions. f. α) − L(P. there is a partition P with 0 ∈ P (eg take a renement if necessary) and U (P. we can nd P such that U (P.xp+1 ] x∈[xp . α. f. f.xp+1 ] inf f (x)) = U (P.xp+1 ] f (x) − x∈[xp . Then. β1 ) = ( sup f (x) − x∈[xp . β1 ) − L(P. (Exercise 6. β2 (0) = 1. Proof. α) + supP L(P. f ) P P We see. if 0 ≤ x < δ . and β3 (0) = 2 (a) Claim. Then. α) + L(P. By the above. f ) = j =1 n f (xj )(α(xj ) − α(xj −1 )) + j =1 α(xj −1 )(f (xj ) − f (xj −1 )) = j =1 f (xj )α(xj ) − f (xj −1 )α(xj −1 ) = f (b)α(b) − f (a)α(a) As we may take common renements in evaluating inf P U (P. f ∈ R (β1 ) if and only if f (0+) = f (0) and. so α ∈ R (f ). α. n U (P. Rm a maximizing sequence of partitions for the sup. x > 0 for all j . we have |f (x) − f (0)| ≤ ( sup x∈[xp . f. α) + sup L(P. that n n U (P. Show that α ∈ R (f ) and that ˆ a b ˆ f dα + a b αdf = f (b)α(b) − f (a)α(a) Solution. 1] given by −1 = x0 < x1 < · · · < xn = 1 and suppose 0 ∈ P (say U (P. f. Let > 0. f. f ) Let > 0. Now. if P is notated as above. then we may evaluate this expression by taking the limit as m → ∞ with the partitions Pm = Qm ∪ Rm ). f. Let f be a bounded function on [−1.xj ] f (x) = f (xj ) and x∈[xj −1 . f. f. b] given by a = x0 < x1 < · · · < xn = b.3) Dene functions βj for j = 1. α. α) = j =1 (f (xj ) − f (xj −1 ))(α(xj ) − α(xj −1 )) = U (P. f. f ) − L(P. Put δ = xp+1 − xp .xj ] inf f (x) = f (xj −1 ) and similarly sup x∈[xj −1 . 3. Then. Suppose f ∈ R (α). ´1 −1 f dβ1 = f (0).xj ] inf α(x) = α(xj −1 ) Thus. α) < . If P is a partition of [a. 0 = xp ). ˆ a b ˆ f dα + a b αdf = inf U (P. f. Suppose f ∈ R (β1 ). 1]. 3 as follows: set βj (x) = 0 if x < 0 and βj (x) = 1 if 1 . α.2.xj ] α(x) = α(xj ) and x∈[xj −1 . α. α) − L(P. f ) − L(P. β1 ) < 2 . set β1 (0) = 0. α : [a. f. α. Let P be a partition of [−1. f ) (ie if Qm is a minimizing sequence of partitions for the inf. β1 ) − L(P. then see sup x∈[xj −1 . f. in that case. As f ∈ R (α). β1 ) − L(P. Let f. f ) < . 2.

f. f. β2 ) − L(P. δ . f. 2 U (P. p + 1. Suppose f ∈ R (β3 ). Then.xp ] f (x) − x∈[xp−1 .xp ] inf f (x)) = U (P. U (P. f. f. we have U (P. ´1 −1 f dβ2 = f (0).xp+1 ] inf f (x)) = 2(U (P.xp ] (c) Claim. Then. Proof. In this case we see inf U (P.xp ] inf f (x)) as β1 (xj ) − β1 (xj −1 ) is 0 if j = p and 1 if j = p. 1. 1. β2 ) = inf ( P P sup f (x)) = f (0−) = f (0) x∈[xp−1 . for P given by −1. β3 ) = as β1 (xj ) − β1 (xj −1 ) is 0 if j = p. Then.xp ] x∈[xp−1 . Then. f. Let > 0 and let δ ∈ (0. f. f. there is a partition P with 0 ∈ P (eg take a renement if necessary) and U (P. Then.xp ] x∈[xp . β1 ) = inf ( P P sup x∈[xp . Let > 0 and let δ ∈ (0. Then.xp ] inf f (x)) ≤ 2 so f ∈ R (β2 ). Suppose f ∈ R (β2 ). δ Then. f. 1) be such that −δ < x ≤ 0 =⇒ |f (x) − f (0)| < .xp+1 ] inf f (x)) = ( sup f (x)−f (0)+f (0)− x∈[xp . f.xp+1 ] x∈[xp−1 .xp+1 ] x∈[xp . f. for P given by −1. Put δ = xp − xp−1 . in that case. 1) be such that 0 ≤ x < δ =⇒ |f (x) − f (0)| < . − 2 .xp ] x∈[xp−1 . In this case we see inf U (P.xp+1 ] x∈[xp . Let P be a partition of [−1. f ∈ R (β2 ) if and only if f (0−) = f (0) and. β3 )) < 2 3 . Now.xp ] inf f (x))+( sup f (x)− x∈[xp . f. suppose f (0+) = f (0). f. if −δ < x ≤ 0. β2 )−L(P.xp+1 ] f (x)) = f (0+) = f (0) (b) Claim. β2 ) − L(P. β3 )−L(P. 0. Now. β3 ) < .xp ] x∈[xp−1 . f ∈ R (β3 ) if and only if f is continuous at 0. β1 )−L(P.so f (0+) = f (0).xp+1 ] 1 2 U (P. there is a partition P with 0 ∈ P (eg take a renement if necessary) and U (P. Put δ = min(xp − xp−1 . 1] given by −1 = x0 < x1 < · · · < xn = 1 and suppose 0 ∈ P (say 1 1 ( sup f (x) − inf f (x)) + ( sup f ( x) − inf f (x)) 2 x∈[xp−1 . f. f. Let P be a partition of [−1. we have Then.xp+1 ] inf f (x)) ≤ 2 so f ∈ R (β1 ).xp+1 ] x∈[xp .xp ] 2 x∈[xp . if |x| < δ . f. f. 0. 0 = xp ). β2 ) − L(P. Let > 0. we have |f (x)−f (0)| ≤ ( sup f (x)− x∈[xp−1 . xp+1 − xp ). f. 1] given by −1 = x0 < x1 < · · · < xn = 1 and suppose 0 ∈ P (say 0 = xp ). β2 ) = ( sup x∈[xp−1 . β3 ) − L(P.xp ] x∈[xp−1 . p + 1 and if j = p. β1 ) = ( sup f (x)− x∈[xp . β2 ) = ( sup f (x)− x∈[xp−1 . Let > 0.xp ] inf f (x)) = ( sup f (x)−f (0)+f (0)− x∈[xp−1 . we have |f (x) − f (0)| ≤ ( sup f (x) − x∈[xp−1 . β3 ) − L(P. β2 ) < so f (0−) = f (0). β2 ) < . suppose f (0−) = f (0).

f is decreasing in u until the critical point f (u0 ) = 0 and then increasing for −1 u ≥ u0 . so this is increasing in u. m. . f. 1 f (x)dx is an increasing function of A as f ≥ 0. we see p > 1. 1 Then. Let A > 1 and suppose m ≤ A < m +1 where m ∈ Z. . m + 1]. f. Chose m ∈ Z such that n=2 f (n) > M .xp+1 ] 2 2 x∈[xp−1 . 1∞ f (x)dx converges if and only if 1A f (x)dx is bounded above uniformly in A. ˆ 1 m+1 m m f (x)dx ≥ L(P. Thus. Dierentiating with respect to u. Let M ∈ R. Proof. (Exercise 6. Suppose f : [1. β3 )−L(P. For u = 0. so ´∞ 1 f (x)dx converges. Moveover equality occurs if and only if up = v q . m + 1] given by xk = k + 1 for k = 0. δ δ Then. . namely u0 = v p−1 . This is up = v . which has a unique 0 1 solution for u0 ≥ 0. for P given by −1. q > 0 be such that up p + 1 q = 1. ∞ k=1 f (k ) is an upper bound for ´A 1 f (x)dx independent of A. x) = k=1 f (xk )(xk − xk−1 ) = k=2 f (k ) > M Thus. x) for any partition P of [1. we see vq 1 this is q ≥ 0. f. β3 ) = inf ( ( sup f (x)) + ( sup f (x)) = f (0) P P 2 x∈[xp−1 . We have f (u0 ) = 1 up vq v p−1 vq 0 + − u0 v = + − v p−1 v p q p q p 4 . Then.10 a-c) (a) Claim. f. Then. then uv ≤ + vq q . ´A f (n) converges. ´A ´ ´ Now. 1. suppose ∞ n=1 f (n) diverges. 1 f (x)dx ≤ ´ m+1 f (x)dx ≤ U (P. ∞). Proof.xp ] 2 x∈[xp . ∞) is monotonically decreasing.xp+1 ] (d) This was proven above. p q Fix v ≥ 0 and consider the function f (u) = up + vq − uv dened on [0. as M was arbitrary. ∞ n=1 4. Suppose ∞ n=1 m m m ∞ U (P. 0. we have U (P. . suppose limx→0 f (x) = f (0). . . so to show the result we evaluate f at u0 where f (u0 ) = 0.xp ] x∈[xp . 1) be such that |x| < δ =⇒ |f (x) − f (0)| < . as f is decreasing. as f is decreasing. (Exercise 6. m. m Now. .xp ] 2 x∈[xp . Let p. − 2 . ´A 1 f (x)dx is not bounded above independent of A and so does not converge. Let P be the partition of [1.so limx→0 f (x) = f (0). In this case we see 1 1 inf U (P. ´ We note by denition that 1∞ f (x)dx converges if and only if limA→∞ 1A f (x)dx converges. Thus. ∞) → [0. Let > 0 and let δ ∈ (0. . If u ≥ 0. f. we have f (u) = up−1 − v . x) = k=1 f (xk−1 )(xk − xk−1 ) = k=1 f ( x k −1 ) = k=1 f (k ) ≤ k=1 f (k ) Thus. ´∞ 1 f (x)dx converges if and only if ´ f (n) converges. 2 .8) Claim. v ≥ 0. Now. Consider P given by xk = k + 1 for k = 0. f. 1 p 5. β3 ) = 1 1 1 1 ( sup f (x)− inf f (x))+ ( sup f (x)− inf f (x)) ≤ 2 + 2 = 2 2 x∈[xp−1 . From p +1 q = 1.xp+1 ] so f ∈ R (β3 ).

we see ( inf |f (x)|)p = inf [xj −1 . if f p = 0.Solving 1 p + 1 q = 1 for q gives q = p p−1 . With the above. so 1+p−1 vq vq + − v p−1 = v q − v q = 0 p q 1 f (u0 ) = Thus. Now. say 0 ≤ Now. g ≥ 0. Indeed. α) = 0 (as |f |p ≥ 0). Proof. b] given by x0 < · · · < xn . Then. g ∈ R (α) are complex functions. so by (b) we have a F Gdα ≤ 1. Consider F = | f p and G = g q . (b) Suppose f. We have | a Claim. for any xed P we must have L(P. Claim. so by (a) we see f (x)g (x) ≤ [a. so supP L(P. suppose f p = 0. G ≥ 0. α) = 0. Moreover. suppose f ˆ |f g |dα = a b We use the notation f p = ( a |f |p dα)1/p and g f| |g | 0. First. g is bounded. g (x).xj ] (|f (x)|p ) = 0 or α(xj ) − α(xj −1 ) = 0 If P is a partition of [a. |f |p . f. Then. Hence. g ∈ R (α). ´ b f gdα| = 0. so it suces to show a |f |dα = 0. We show | a ´b ´b ´b |g | ≤ M . F. f has a unique minimum (as f is strictly increasing) at u = v p−1 . xj ] given by P . then ´b p f p = a |f |p dα = 0. ´ q p .xj ] (|f (x)|p ) [xj −1 . this gives ˆ b b p 1 f p ˆ g | q a b f gdα| ≤ 1 so | ´b a f gdα| ≤ f p g q as claimed. b]. which is the same as up = v q . and at this point it attains the value 0. we have 0 ≤ f (x). (c) Suppose f. b] this becomes ˆ b ˆ b f gdα ≤ a a fp gq 1 1 + dα = + = 1 p q p q as desired. Proof. f gdα ≤ 1 f (x)p p ) + g (x q . and ´b a ´b a f p dα = 1 = ´b a g q dα. so |g | is bounded. g q > 1 f p ˆ g | q a b f gdα| ≤ ˆ 1 f p ˆ g q a b b F Gdα We see ´b p |f | dα |f |p a =1 F dα = p dα = ´ b f p a a |f |p dα a ´b q ´b and likewise a G dα = 1. so this shows that for every [xj −1 .xj ] 5 . | a f gdα| ≤ | a |f |M dα. we either have inf [xj −1 . |f |p . ˆ b ˆ f gdα| ≤ ( a b |f | dα) p 1/p ˆ ( a b |g |q dα)1/q ´b = ( a |g |q dα)1/q . Integrating over q For x ∈ [a.

Show 2 ≤ f −g + g−h 2 Let F = f − h and G = g − h.2). it suces ˆ a b ˆ |F + G| dα ≤ a 2 b ˆ |F | + 2|F ||G| + |G| dα = F 2 2 2 2 b +2 a |F ||G|dα + G 2 2 Now. if g q = 0. 2xf (x) = cos(x2 ) − cos((x + 1)2 ) + r (x) Proof. α) = 0 for all P . 2 + G 2 . 1 1 |f (x)| < + + 2x 2(x + 1) ˆ (x+1)2 du 4u 3 2 = x2 1 1 −1 (x+1)2 1 1 1 1 1 + +( 1 )|u=x2 = + + − = 2x 2(x + 1) 2 x 2( x + 1) 2 x 2( x + 1) x 2 2u 1 4u 2 3 Note the inequality is strict here as both cos(u) 1 3 and 4u 2 are not the same (see exercise 6. (Exercise 6. From the left hand side. 2 2 6. g. ˆ (x+1)2 r ( x) = −2x cos((x + 1)2 ) + cos((x + 1)2 ) − 2x 2(x + 1) cos(u) x2 du 4u 2 3 = cos((x + 1)2 ) − 2x (x + 1) (x+1)2 cos(u) x2 du 4u 2 3 6 . x + 1] and these functions c x where |r(x)| < for some constant c.10. Dene f (x) = 1 x ´ x+1 x sin(t2 )dt for x > 0 ˆ ˆ sin(t )dt = x x2 2 Let u = t2 . are continuous on [x. Suppose f.xj ] |f (x)| = 0 or α(xj ) − α(xj −1 ) = 0 so we have L(P. this is − cos(u) 2u 1 2 |u=x2 − (x+1)2 ˆ (x+1)2 cos(u) x2 du 4u 3 2 = cos(x2 ) cos((x + 1)2 ) − − 2x 2(x + 1) (x+1)2 cos(u) x2 du 4u 2 3 Hence. so we wish to show F + G 2 ≤ F 2 to show F + G 2 2 ≤ ( F 2 + G 2 ) . |f |. then | ´b a f gdα| = 0. |f (x)| < Proof. so the claim holds.Hence. h ∈ R (α).11) For u ∈ R (α). By the above. we have 2 F +G 2 2 ´b a |F ||G|dα ≤ 2 F 2 2 2 2 G 2 . 7. For this. Thus. α)P = 0 p Likewise. (b) Claim. let u f −h ´b 1 = ( a |u|2 dα) 2 . |f |. ˆ a b |f |dα = sup L(P. from exercise 6. (Exercise 6. ˆ Put r(x) = 2xf (x) − cos(x2 ) + cos((x + 1)2 ). xj ] we have inf [xj −1 . so du = 2tdt and x+1 (x+1)2 sin(u) du 2u 2 ˆ 1 Integrating by parts. so we have + G 2 2 ≤ F +2 F 2 G =( F 2 + G 2 )2 as claimed.13) (a) Claim. we have Proof. on [xj −1 .

Then. Let M > 0 and nd N > M such that 2 √2π (n + 1) − 2 2πn < δ for n ≥ N . (d) Claim. we have cos(1) cos(A2 ) − − 2 2A ˆ 1 A2 sin(t2 )dt = 1 cos(u) u2 3 du and ´ A2 1 cos(u) 3 u2 du is absolutely convergent. We have √ √ 2 cos(x2 n ) − cos((xn + 1) ) = cos(2πn) − cos(2πn + 2 2πn + 1) = 1 − cos(2 2πn + 1) where we have used cos(A + B ) = cos(A) cos(B ) − sin(A) sin(B ). (c) Claim. Let > 0. Proof. cos(A2 ) 2A → 0 as A → ∞. 7 . 1 We know x|f (x)| < 1 by (a). As above. Thus. we see√ there is an x ≥ M with x = 2 2πn for some n ≥ N and |x − (2m + √1)π | < δ for some m ∈ Z. ´∞ 1 A It suces to show ˆ sin(t2 )dt converges. Consider the sequence formed by taking xn = 2πn for n ∈ Z+ . Proof. | cos(2 2πn) + 1| < . We know that this has lower limit ≥ −1.and so |r(x)| ≤ 1 + 2x x+1 ˆ (x+1)2 du 4u 3 2 = x2 1 1 1 1 x+1−x 2 + 2 x( − )= + x( )= x+1 2x 2(x + 1) x+1 x(x + 1) x+1 so c = 2 works. The proof that √ the lower limit of xf (x) = −1 is similar with π (2n + 1) in place of 2πn. we need only show cos(2 2πn + 1) has lower limit −1. as 2 2πn → ∞as n → ∞. √ ´∞ 0 sin(t2 )dt converges. From (b). Hence. we have | cos(x) + 1| < √ by periodicity. we have xf (x) = 2 (cos(x2 ) − cos((x + 1)2 ) + r(x)) where 2 2 r(x) → 0 as x → ∞. from which it follows that the lower limit of cos(2 2πn + 1) is −1. if |x − (2m √ + 1)π | < δ . The upper and lower limits of xf (x) are 1 and −1 respectively. Let δ > 0 be such that |x − π | < δ =⇒ | cos(x) + 1| < . so it suces to show the upper limit of cos(x ) − cos((x + 1) lower limit √ ) is 2 and the 2 2 of cos(x ) − cos((x + 1) ) is −2. so this converges. Then.